2021
DOI: 10.3390/healthcare9060661
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Workplace Safety Climate among Healthcare Workers during the COVID-19 Pandemic in Low and Middle Income Countries: A Case Study of Nigeria

Abstract: The COVID-19 pandemic has presented several organizations with the opportunity to review their operational strategies, as well as the existing safety climate within their establishments. The healthcare sector is not an exception, especially those in Low and Middle Income Countries (LMICs), where most safety systems are not robust when compared with developed countries. The study aim is to assess the occupational safety climate among healthcare workers (HCWs) in LMICs using Nigeria as a case study. A cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Due to lack of official data in the public domain, a projection of over 14,000,000 active individuals engaged in farming actives as their primary source of livelihood in the study area comprising of six states (Bauchi, Benue, Gombe, Plateau, Nassarawa, and Kaduna) was made. To determine the sample size for the study, Fisher's formula [27] for estimating single proportions and estimation for minimum sample size was applied, and an estimated sample size of 385 was made.…”
Section: Sample Sizementioning
confidence: 99%
“…Due to lack of official data in the public domain, a projection of over 14,000,000 active individuals engaged in farming actives as their primary source of livelihood in the study area comprising of six states (Bauchi, Benue, Gombe, Plateau, Nassarawa, and Kaduna) was made. To determine the sample size for the study, Fisher's formula [27] for estimating single proportions and estimation for minimum sample size was applied, and an estimated sample size of 385 was made.…”
Section: Sample Sizementioning
confidence: 99%
“…In accordance with Moda et al [ 14 ] previous research, this study, used a cross-sectional design with a convenient snowball sampling technique to reach out to the target participants’ to assess the safety climate among professionals in the power sector. Moda et al [ 14 ] used the same technique to collect data Snowball sampling is a non-probability sampling method [ 26 ]; that is best suited to small, difficult to reach populations. This sampling method entails primary data sources that recommend additional potential primary data sources for use in the research.…”
Section: 0 Materials and Methodologymentioning
confidence: 99%
“…Previous studies have focused on industries such as aviation, construction [ 12 , 13 ], transportation, manufacturing plants, and oil and gas [ 14 ], and the majority of safety climate studies have been conducted in Western countries, specifically Australia, the United Kingdom, the United States, and Canada [ 12 ]. In contrast, this research focusses on the power sector, in the context of Pakistan, a developing country.…”
Section: 0 Introductionmentioning
confidence: 99%
“…The section that deals with descriptive cross-sectional quantitative studies have sections that assess the relevance of the sampling to the research question, the representative of the sample to the target population, appropriateness of the measurements, the risk of nonresponse is low, and whether the statistical method adopted responded appropriately to the research question. All the studies identified in this category had all the responses being affirmative to each type except three [14,[16][17][18][19][20][21][22][23][24][25][26]. The three studies failed to meet the criteria requiring the study sample to represent the population [17,19,26].…”
Section: Quality Appraisalmentioning
confidence: 99%